Does the Severity of Students' Pre-Intervention Math Deficits Affect Responsiveness to Generally Effective First-Grade Intervention?. (January 2019) - Fuchs, Lynn S.; Fuchs, Douglas; Gilbert, Jennifer K.
The purpose of this analysis was to assess whether effects of first-grade mathematics intervention apply across the range of at-risk learners' initial skill levels. Students were randomly assigned to control ( n = 213) and two variants of intervention ( n = 385) designed to improve arithmetic. Of each 30-minute intervention session (48 over 16 weeks), 25 minutes were identical in the two variants, focused on number knowledge that provides the conceptual bases for arithmetic. The other five minutes provided nonspeeded conceptual practice ( n = 196) or speeded strategic practice ( n = 199). Contrasts tested effects of intervention (combined across variants) versus control and effects between the variants. Moderation analysis indicated no significant interactions between at-risk children's pre-intervention mathematics skill and either contrast on any outcome. Across pre-intervention math skill, effects favored intervention over control on arithmetic and transfer to double-digit calculations and number knowledge, and favored speeded over nonspeeded practice on arithmetic.